Two cyclohexane-type octadecanuclear metalla-macrocycle-based metal organic frameworks and adsorption properties. Issue 28 (8th June 2016) - Chen, Shufang; Hu, Jiyong; Zhao, Jin'an; Zhang, Jin; Yu, Huaibin; Zhi, Shuangcheng; Zhang, Junshuai; Gong, Zhanqiang
Abstract : Two 3D structures with octadecanuclear building units have been achieved, in which complex1 exhibits excellent absorption properties. Abstract : Two novel porous metal–organic frameworks (MOFs) with {M18 (Hbtib)36 } (M = Ni(ii ), Zn(ii )) as the basic building unit, namely, [Ni(Hbtib)2 ] n (1 ) and [Zn(Hbtib)2 ·H2 O] n (2 ) [H2 btib = 4-((2-butyl-5-(2-carboxy-3-(thiophen-2-yl)prop-1-enyl)-1 H -imidazol-1-yl)methyl)] were synthesized using solvothermal reactions. Gas adsorption (N2, H2, CO2 and CH4 ) studies show that the desolvated solid1 is a highly effective absorbent for CO2 over CH4 at 273 and 298 K. The results suggest that1 has potential application in gas separation or purification. In addition, the photoluminescence properties of2 were also investigated.